Smectite slurry, clay film, and method for producing smectite slurry
By dispersing multi-metal fixed-type smectite in a polar medium with ammonia and organic solvents and heat treatment, the method addresses lithium scarcity and safety issues, achieving stable, small-particle slurry for versatile water-resistant films.
Patent Information
- Application Number
- JP2021119509
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-20
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-07-20
AI Technical Summary
Existing technologies for lithium-fixing montmorillonite slurry are limited by lithium resource scarcity, high cost, and safety concerns, and lack versatility for general-purpose applications, with large particle sizes leading to defects in water-resistant films.
A method involving the dispersion of multi-metal fixed-type smectite in a polar medium containing ammonia, water, and polar organic solvents, followed by heat treatment, to achieve a slurry with particle diameters of 20 μm or less and improved stability.
The resulting slurry provides enhanced water resistance and stability, enabling the formation of defect-free water-resistant films with broader industrial applications and reduced resource dependency.
Smart Images

Figure 0007627038000001 
Figure 0007627038000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a smectite slurry, a clay film, and a method for producing a smectite slurry. [Background technology]
[0002] Industrial clays are used in a wide range of fields, including as thickeners, binders, rheology modifiers, inorganic binders, civil engineering muds, waterproofing materials, and cosmetic ingredients. Smectite is known as a type of industrial clay. The general crystal structure of smectite consists of a 2:1 layered unit crystal layer, in which an alumina octahedron sheet is sandwiched between silicic acid tetrahedron sheets, in which a silicic acid network spreads. In many cases, some of the aluminum atoms in the alumina octahedron sheets, which are the central atoms in the crystalline layers, are replaced by magnesium, which makes the crystalline layers negatively charged, and cations are incorporated between the layers to neutralize the negative charge. In addition, these cations can be exchanged, so smectite exhibits cation exchangeability. The amount of exchangeable cations is called the cation exchange capacity (CEC), and is one of the indicators of smectite's properties.
[0003] It is known that when smectite is subjected to heat treatment, the cations between the layers (protons, sodium ions, potassium ions, lithium ions, cesium ions, ammonium ions, calcium ions, magnesium ions, etc.) are fixed as a result of dehydration. When the cations are fixed, the basic properties of smectite, such as dispersion stability in water, viscosity increase, swelling ability, and cation exchange ability, decrease.
[0004] It has been reported that the functionality of smectite can be enhanced by utilizing the phenomenon of fixation of interlayer cations by the above-mentioned heat treatment. For example, Patent Documents 1 and 2 describe that a clay film with excellent water resistance (water vapor barrier properties) can be obtained by forming a film using an aqueous dispersion of montmorillonite having lithium ions between layers and then subjecting the film to a heat treatment in a dryer. If the water dispersibility (dispersion stability) of lithium-type montmorillonite (lithium-loaded montmorillonite) in which lithium ions are fixed by heating can be improved, it becomes possible to prepare a slurry of the lithium-loaded montmorillonite, and a clay film with excellent water resistance (in this specification, "water resistance" means "water vapor gas barrier property") can be formed simply by applying and drying this slurry. In fact, several techniques for improving the water dispersibility of lithium-loaded montmorillonite have been reported. For example, Patent Document 3 describes that a slurry containing specific amounts of lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and a polar organic solvent having a formamide group has excellent dispersion stability of the lithium-loaded montmorillonite. Patent Document 4 describes that a slurry containing specific amounts of lithium-loaded montmorillonite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and an organic solvent selected from at least acetonitrile and methyl ethyl ketone has excellent dispersion stability of the lithium-loaded montmorillonite. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2008-247719 A [Patent Document 2] JP 2009-107907 A [Patent Document 3] JP 2015-147300 A [Patent Document 4] JP 2018-83728 A Summary of the Invention [Problem to be solved by the invention]
[0006] The techniques of Patent Documents 3 and 4 above make it possible to prepare a slurry in which lithium-loaded montmorillonite is stably dispersed, and it is expected that the industrial application field of lithium-loaded montmorillonite as a functional material will expand. However, in these techniques, the metal used for the interlayer ion is limited to lithium. Lithium has a Clarke number (the proportion of elements present in the earth's crust) of 0.006 mass%, ranking 27th in the order of abundance of metal elements, making it a rare resource. In addition, the demand for lithium-ion batteries is also strong, and it is predicted that the demand will continue to expand in the future. Therefore, lithium is chronically in short supply, and its price tends to be unstable and expensive. If it is possible to achieve the same high water resistance as lithium-loaded montmorillonite with polyvalent metal-loaded smectite that has a more abundant polyvalent element (large Clarke number) between layers and is partially fixed by a process such as firing, it can be made into a cheaper and more versatile material, which will enable it to be developed into many applications. In addition, the organic solvent required for slurrying may be a concern regarding its safety to living organisms. Therefore, if it were possible to disperse polyvalent metal-immobilized smectite in an organic solvent that is highly safe and versatile and can be used for general-purpose paints and coating materials, and then turn it into a slurry, the versatility of the technology would be further enhanced.
[0007] When a slurry of lithium-loaded montmorillonite is used to form a film with enhanced barrier function such as a water-resistant film, it is important that the lithium-loaded montmorillonite is dispersed in the form of fine particles in the slurry. For example, if the particle size of the lithium-loaded montmorillonite dispersed in the slurry is large (if it is aggregated), the film formed using this slurry is likely to have fine defects, making it difficult to achieve the desired water resistance. There has been no report to date of forming a slurry of polyvalent metal-immobilized smectite and using it as a waterproof film as described above.
[0008] An object of the present invention is to provide a slurry in which polyvalent metal-fixed smectite, which has abundant polyvalent metal ions immobilized in a clay layer and has reduced cation exchangeability and water dispersibility, is stably dispersed and the particle size of the dispersed polyvalent metal-fixed smectite is sufficiently small, a clay film using the slurry, and a method for producing the slurry. [Means for solving the problem]
[0009] The present inventors have conducted extensive research in view of the above problems. As a result, they have found that, in preparing a dispersion of polyvalent metal-fixed smectite, ammonia and a specific organic solvent are mixed in a dispersion medium (water), and then this mixture is mixed with polyvalent metal-fixed smectite powder having a cation exchange property of a certain level or less, and the mixture is then subjected to a heat treatment, whereby the polyvalent metal-fixed smectite can be stably dispersed in a finer state in the dispersion medium, and a slurry having excellent dispersion stability over time can be obtained. The present invention has been completed through further research based on these findings.
[0010] The above object of the present invention has been achieved by the following means. [1] A smectite slurry comprising a polyvalent metal-fixed smectite having a cation exchange capacity of 50 meq / 100 g or less dispersed in a polar medium containing ammonia, water, and a polar organic solvent, the polyvalent metal-fixed smectite in the dispersed state having a particle size of 20 μm or less. [2] The smectite slurry according to [1], wherein the polyvalent metal-fixed smectite is a divalent metal-fixed smectite and / or a trivalent metal-fixed smectite. [3] The smectite slurry according to [2], wherein the divalent metal-fixed smectite is one or more of Ca-fixed smectite, Mg-fixed smectite, Fe-fixed smectite, Zn-fixed smectite and Cu-fixed smectite. [4] The smectite slurry according to [2] or [3], wherein the trivalent metal-fixed smectite is Al-fixed smectite and / or Fe-fixed smectite. [5] The smectite slurry according to any one of [1] to [4], wherein the smectite is montmorillonite. [6] The smectite slurry according to any one of [1] to [5], wherein the polar organic solvent is one or more of an ether solvent, an alcohol solvent, a ketone solvent, an ester solvent, and a nitrogen-containing solvent. [7] The smectite slurry according to any one of [1] to [6], wherein the content of the water in the polar medium is 4 to 90 mass %. [8] The smectite slurry according to any one of [1] to [7], wherein the content of the ammonia in the smectite slurry is 0.1 mmol or more per 1 g of the polyvalent metal-immobilized smectite. [9] The smectite slurry according to any one of [1] to [8], which is subjected to a heat treatment at 35 to 100°C.
[10] The smectite slurry according to any one of [1] to [9], wherein the polyvalent metal-fixed smectite is obtained by subjecting a polyvalent metal-type smectite to a heat treatment at 200 to 700°C.
[11] A clay film using the smectite slurry according to any one of [1] to
[10] .
[12] A method for producing a smectite slurry, comprising mixing a polyvalent metal-fixed smectite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and a polar organic solvent, and subjecting the mixture to a heat treatment at 35 to 100°C to obtain a slurry in which the polyvalent metal-fixed smectite is dispersed in the polar medium.
[13] The method for producing a smectite slurry according to
[12] , wherein the polyvalent metal-fixed smectite is a divalent metal-fixed smectite and / or a trivalent metal-fixed smectite.
[14] The method for producing a smectite slurry according to
[13] , wherein the divalent metal-fixed smectite is one or more of Ca-fixed smectite, Mg-fixed smectite, Fe-fixed smectite, Zn-fixed smectite and Cu-fixed smectite.
[15] The method for producing a smectite slurry according to
[13] or
[14] , wherein the trivalent metal-fixed smectite is Al-fixed smectite and / or Fe-fixed smectite.
[16] The method for producing a smectite slurry according to any one of
[12] to
[15] , wherein the smectite is montmorillonite.
[17] The method for producing a smectite slurry according to any one of
[12] to
[16] , wherein the polar organic solvent is one or more of an alcohol solvent, a ketone solvent, an ether solvent, an ester solvent, and a nitrogen-containing solvent.
[18] The method for producing a smectite slurry according to any one of
[12] to
[17] , wherein the content of the water in the polar medium is 4 to 90 mass %.
[19] The method for producing a smectite slurry according to any one of
[12] to
[18] , wherein the amount of the ammonia mixed is 0.1 mmol or more per 1 g of the polyvalent metal-immobilized smectite.
[20] The method for producing a smectite slurry according to any one of
[12] to
[19] , wherein the particle size of the polyvalent metal-fixed smectite dispersed in the polar medium is 20 μm or less. Effect of the Invention
[0011] The smectite slurry of the present invention (hereinafter also simply referred to as "slurry of the present invention") has polyvalent metal-fixed smectite having low water dispersibility and a cation exchange ability below a specific level, which is finely divided and stably dispersed, and also has excellent dispersion stability over time. Furthermore, the clay film of the present invention is a film formed using the slurry of the present invention, and is excellent in water resistance and production efficiency. Furthermore, according to the method for producing a smectite slurry of the present invention (hereinafter also simply referred to as "the method for producing a slurry of the present invention"), it is possible to obtain a slurry in which polyvalent metal-fixed smectite, which has low water dispersibility and a cation exchange ability below a specific level, is dispersed in a finer, more stable form and which also has excellent dispersion stability over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments except as defined in the present invention.
[0013] [Smectite slurry] The slurry of the present invention is a slurry in which polyvalent metal-immobilized smectite having a cation exchange capacity (CEC) of 50 meq (milliequivalent) / 100 g or less is dispersed in a polar medium. This polar medium contains ammonia, water, and a polar organic solvent, and the polyvalent metal-immobilized smectite is dispersed in the polar medium in the form of fine particles having a particle size of 20 μm or less. The slurry of the present invention may contain components other than the above-mentioned components within the range that does not impair the effects of the present invention. Each component constituting the smectite slurry of the present invention will be described in detail below.
[0014] <Polyvalent metal fixed smectite> The polyvalent metal-immobilized smectite used in the present invention constitutes a dispersoid in the slurry of the present invention.
[0015] The type of the smectite is not particularly limited and can be appropriately selected depending on the purpose. The smectite is preferably one or more selected from montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, and stevensite, more preferably one or more selected from montmorillonite, saponite, and stevensite, and even more preferably montmorillonite.
[0016] The polyvalent metal fixed smectite used in the present invention is a smectite in which at least a part of the polyvalent metal ions is fixed to the vacant sites (vacant seats) of the octahedral or tetrahedral sheets of the clay layer. The polyvalent metal fixed smectite is obtained by fixing the interlayer polyvalent metal ions to the vacant sites of the octahedral or tetrahedral sheets by high-temperature treatment of the polyvalent metal smectite (for example, heat treatment at 200 to 700 ° C. as described later). By fixing the polyvalent metal ions, the crystalline layers of the smectite are closed, and the hydrophilicity is greatly reduced. This is thought to be because the polyvalent metal ions move to and are fixed in the vacant seats of the octahedral or tetrahedral sheets of the clay crystal, which electrically neutralizes the clay crystal and closes the interlayers, making it difficult for water molecules to enter (hydration of the interlayer cations is difficult to occur).
[0017] The CEC of the polyvalent metal-fixed smectite used in the present invention is 50 meq / 100g or less, preferably 45 meq / 100g or less, and more preferably 40 meq / 100g, from the viewpoint of imparting dispersibility in low-polarity solvents and low-polarity resins, color development, water vapor barrier properties, etc. The CEC of the above-mentioned polyvalent metal-fixed smectite is usually 1 meq / 100g or more, may be 5 meq / 100g or more, or may be 8 meq / 100g or more. For example, divalent and / or trivalent metal smectite usually has a CEC of about 80 to 150 meq / 100 g, but at least a portion of the polyvalent metal ions can be fixed by high-temperature treatment described below, reducing the CEC to 50 meq / 100 g or less. In the present invention, the CEC of the polyvalent metal-fixed smectite means the CEC of the polyvalent metal-fixed smectite dispersed in a polar medium.
[0018] The polyvalent metal-fixed smectite used in the present invention is a smectite in which polyvalent metal ions are present in a state of being fixed between clay layers, as described above. In particular, the smectite is preferably a divalent and / or trivalent polyvalent metal-fixed smectite (i.e., one or more types of polyvalent metal-fixed smectite selected from divalent metal-fixed smectite and trivalent metal-fixed smectite).
[0019] The type of polyvalent metal in the divalent polyvalent metal-fixed smectite is not particularly limited, and for example, one or more divalent metal-fixed smectites selected from Ca-fixed smectite, Mg-fixed smectite, Ba-fixed smectite, Cu-fixed smectite, Zn-fixed smectite, Sn-fixed smectite, Fe-fixed smectite, Pb-fixed smectite, Co-fixed smectite, and Mn-fixed smectite can be used. Among these, from the viewpoints of easy availability, functionality, and safety, it is preferable to use one or more divalent metal-fixed smectites selected from Ca-fixed smectite, Mg-fixed smectite, Ba-fixed smectite, Fe-fixed smectite, Cu-fixed smectite, and Zn-fixed smectite, and it is more preferable to use one or more divalent metal-fixed smectites selected from Ca-fixed smectite, Mg-fixed smectite, Fe-fixed smectite, Cu-fixed smectite, and Zn-fixed smectite.
[0020] The type of polyvalent metal in the trivalent polyvalent metal-fixed smectite is not particularly limited, and examples thereof include one or more trivalent metal-fixed smectites selected from Al-fixed smectite, Fe-fixed smectite, Mn-fixed smectite, Co-fixed smectite, Sn-fixed smectite, and Cr-fixed smectite. Of these, it is preferable to use a trivalent metal-fixed smectite selected from Al-fixed smectite and / or Fe-fixed smectite, from the viewpoints of availability, functionality, and safety.
[0021] In addition, the polyvalent metal fixed smectite usually contains sodium ions (Na + ), potassium ion (K + In the polyvalent metal fixed smectite used in the present invention, Na + and K + The total amount of leached ions is preferably 1 to 30 meq / 100 g, more preferably 1 to 20 meq / 100 g, and even more preferably 1 to 10 meq / 100 g.
[0022] The polyvalent metal-fixed smectite used in the present invention can be obtained, for example, by fixing polyvalent metal ions (polyvalent cations) present between layers of the crystal structure of polyvalent metal-type smectite by high-temperature treatment or the like. The temperature conditions of the high-temperature treatment for fixing the polyvalent cations are not particularly limited as long as the polyvalent cations can be at least partially fixed. As described above, the smaller the CEC, the more the water vapor barrier property and oxygen barrier property of the layer formed using the aqueous dispersion containing the polyvalent metal-fixed smectite tend to be improved. Therefore, from the viewpoint of efficiently fixing the polyvalent metal ions and reducing the CEC, it is preferable to heat at 200°C or higher. The temperature of the heat treatment is more preferably 200 to 700°C, even more preferably 250 to 650°C, particularly preferably 300 to 650°C, and most preferably 350 to 600°C. By heating within the above temperature range, the CEC can be more efficiently reduced and at the same time, the dehydration reaction of the hydroxyl group in the smectite can be suppressed. The heat treatment is preferably performed in an open electric furnace. In this case, the relative humidity during heating is 5% or less, and the pressure is normal pressure. The time of the heat treatment is not particularly limited as long as the polyvalent cations can be fixed. From the viewpoint of production efficiency, the time for the heat treatment is preferably 0.5 to 48 hours, and more preferably 1 to 24 hours.
[0023] The fact that the polyvalent metal ions have been immobilized by the heat treatment can be determined by measuring the CEC and the amount of ion elution (Lc: Liquid Chromatography) of the target ions. If the CEC and Lc values of the target ions after the partial immobilization treatment (e.g., the heat treatment) are lower than the CEC and Lc values of the target ions before the partial immobilization treatment, this indicates that at least a portion of the target ions has been immobilized between the layers of the smectite crystal structure.
[0024] In this specification, the "polyvalent metal-type smectite" that can be used for producing the polyvalent metal-fixed smectite is preferably a polyvalent metal-type smectite in which the amount of polyvalent metal ions (i.e., the amount of leached polyvalent metal ions, unit: meq / 100 g, the same below) in the amount of leached cations of the smectite (i.e., the total amount of leached cations, unit: meq / 100 g, the same below) is 60% or more, more preferably a polyvalent metal-type smectite in which the amount of leached polyvalent metal ions in the amount of leached cations is 70% or more, and even more preferably 80% or more. The amount of leached polyvalent metal ions in the amount of leached cations of the polyvalent metal-type smectite may be 100%, but is usually 99% or less. In this specification, when "X-fixed smectite" (X is a type of polyvalent metal) is mentioned, it is preferable that the polyvalent metal-fixed smectite is obtained by using a polyvalent metal-type smectite in which the amount of leached X ions in the amount of leached cations of the polyvalent metal-type smectite used as the raw material is 60% or more. More preferably, the amount of leached X ions in the amount of leached cations of the polyvalent metal-type smectite is 70% or more, and even more preferably 80% or more. The amount of leached X ions in the amount of leached cations of the polyvalent metal-type smectite may be 100%, but is usually 99% or less. In the present specification, the "polyvalent metal-type smectite" preferably has a CEC of more than 50 meq / 100 g. The CEC of the polyvalent metal-type smectite is more preferably 60 to 150 meq / 100 g, even more preferably 70 to 120 meq / 100 g, and even more preferably 80 to 110 meq / 100 g.
[0025] The method for producing the polyvalent metal type smectite (e.g., divalent metal type smectite or trivalent metal type smectite) is not particularly limited, and for example, it can be obtained by adding an aqueous salt solution of the target polyvalent metal ion (e.g., halide, sulfide, sulfate, carbonate, nitrate, acetate, phosphate, phosphite, perchlorate, chlorate) to an aqueous dispersion of natural or synthetic sodium type smectite and carrying out cation exchange. By adjusting the amount of salt added to the dispersion, the ratio of the target polyvalent metal ion to the amount of leached cations of the obtained smectite can be appropriately adjusted. In addition, for example, polyvalent metal type smectite can also be obtained by a column method or a batch method using a cation exchange resin.
[0026] The content of the polyvalent metal-fixed smectite in the slurry of the present invention is not particularly limited and can be appropriately adjusted depending on the purpose. From the viewpoint of ensuring the fluidity of the slurry and making the kneading and stirring steps practically possible, the content of the polyvalent metal-fixed smectite in the smectite slurry of the present invention is preferably 1 to 30 mass%, more preferably 2 to 28 mass%, even more preferably 5 to 25 mass%, and even more preferably 9 to 21 mass%. The form of the smectite is not particularly limited, and for example, smectite in the form of powder or dehydrated cake may be used.
[0027] In the slurry of the present invention, the polyvalent metal-fixed smectite is dispersed in a state in which the particle size is 20 μm or less. From the viewpoint of preventing defects in the film formed using the slurry and further enhancing functionality such as water resistance, the particle size is preferably 15.0 μm or less, more preferably 13.0 μm or less, even more preferably 10.0 μm or less, and even more preferably 8.0 μm or less. In the slurry of the present invention, there is no particular lower limit for the particle size of the polyvalent metal-fixed smectite, and it is usually 1.0 μm or more, and may be 1.5 μm or more, or may be 2.0 μm or more. In the present invention, the "particle size" of the polyvalent metal-immobilized smectite in the slurry is a volume-based median size. This particle size can be determined, for example, by a laser diffraction / scattering type particle size distribution measuring device.
[0028] <Ammonia> The polar medium constituting the slurry of the present invention contains ammonia. As the ammonia source, any of ammonia water, gaseous ammonia, and liquid ammonia may be used, but when the slurry is produced under atmospheric pressure, it is preferable to use ammonia water. The content of ammonia in the slurry of the present invention is preferably 0.1 mmol or more per 1 g of polyvalent metal-fixed smectite in the slurry, more preferably 0.2 mmol or more, even more preferably 0.5 mmol or more, even more preferably 0.8 mmol or more, and also preferably 1.0 mmol or more. By setting the content of ammonia to the above-mentioned preferred value, a sufficient number of molecules of ammonia can penetrate between the layers of the clay crystals of the polyvalent metal-fixed smectite, and the solution dispersibility of the polyvalent metal-fixed smectite can be further improved. In addition, in consideration of the generation of ammonia odor and production costs, the content of ammonia in the slurry of the present invention is preferably 10 mmol or less per 1 g of polyvalent metal-fixed smectite in the slurry, more preferably 5 mmol or less, and even more preferably 2 mmol or less. In this specification, "per gram of polyvalent metal-fixed smectite" specifically means per gram of polyvalent metal-fixed smectite contained in the slurry. More specifically, it means per gram of mass of a treated product obtained by removing the polyvalent metal-fixed smectite contained in the slurry from the slurry and treating the removed smectite at a temperature of 200°C for 24 hours. The heat treatment is preferably carried out in an open electric furnace. In this case, the relative humidity during heating is 5% or less, and the pressure is normal pressure. The amount of ammonia per 1 g of polyvalent metal-fixed smectite is obtained by dividing the amount of ammonia (mmol) in the slurry by the mass of the polyvalent metal-fixed smectite in the slurry (i.e., the mass of the treated product obtained by extracting the polyvalent metal-fixed smectite present in the slurry and heat-treating the extracted smectite at a temperature of 200°C for 24 hours) (unit: g). The ammonia content in the slurry can be measured by the indophenol method, the Kjeldahl method, gas chromatography, or ion chromatography.
[0029] <Organic solvent> The polar medium constituting the slurry of the present invention contains a polar organic solvent. The polar organic solvent can be used without any particular limitation as long as it has a polar group (a group containing a heteroatom other than carbon atom and hydrogen atom) and is miscible with water. Examples of the polar organic solvent include ether solvents, alcohol solvents, ketone solvents, ester solvents, and nitrogen-containing solvents, and one or more of these organic solvents can be used (hereinafter, the polar organic solvent may be simply referred to as "organic solvent"). Each of the organic solvents exemplified above has a relatively high polarity and is suitable for swelling the polyvalent metal-fixed smectite.
[0030] The organic solvent used in the present invention is preferably a highly water-soluble (hydrophilic) organic solvent (organic solvent). When polyvalent metal-fixed smectite is dispersed in a polar medium, the dispersion efficiency is high if a certain amount of water is present. Therefore, the organic solvent is preferably one that dissolves water at a concentration of preferably 5% by mass or more, more preferably 7% by mass or more, even more preferably 10% by mass or more, and even more preferably 20% by mass or more at 25°C. In addition, the organic solvent is preferably an organic solvent that is infinitely miscible with water. The organic solvent used in the present invention is preferably an organic solvent having no acid group and which does not undergo any reaction, such as gelation, with the immobilized polyvalent metal smectite. In addition, the organic solvent is preferably liquid at room temperature.
[0031] As the ether solvent, a compound having at least one ether bond in the molecule and exhibiting the above-mentioned water solubility can be suitably used. Examples of such ether solvents include tetrahydrofuran, trioxane, tetrahydropyran, dimethoxyethane, 1,2-diethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, methylal, acetal, low molecular weight polyethylene glycol, polypropylene glycol, crown ether, etc.
[0032] As the alcohol solvent, a compound having at least one hydroxyl group in the molecule and exhibiting the above-mentioned water solubility can be suitably used. Examples of such alcohol solvents include monohydric straight-chain alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentyl alcohol, tert-pentyl alcohol, 3-methyl-2-butanol, and neopentyl alcohol. Furthermore, examples of polyhydric alcohols include 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-butene-1,4-diol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, glycerol, 2-ethyl-2-(hydroxymethyl)-1,3-propanediol, 1,2,6-hexanetriol, and glycerol. In the present invention, an organic solvent having an ether bond as well as a hydroxyl group is not considered to be an alcohol solvent but is included in an ether solvent.
[0033] As the ketone solvent, a compound having at least one ketone group in the molecule and exhibiting the above-mentioned water solubility can be suitably used, such as acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, acetonylacetone, acetylacetone, etc. In addition, even if a solvent has a ketone group, the solvents which fall under the above-mentioned ether solvents and alcohol solvents are not included in the ketone solvents of the present invention.
[0034] As the ester solvent, a compound having at least one ester bond in the molecule and exhibiting the above-mentioned water solubility can be suitably used. Examples of such ester solvents include methyl formate, ethyl formate, methyl acetate, ethyl acetate, 3-methoxybutyl acetate, γ-butyrolactone, ethylene glycol monoacetate, ethylene diacetate, monoacetylene, ethylene glycol monoacetate, ethylene carbonate, propylene carbonate, low molecular weight polyester, etc. In addition, even if a solvent has an ester bond, the solvent also falls under the above-mentioned ether solvent, alcohol solvent, or ketone solvent, and is not included in the ester solvent in the present invention.
[0035] As the nitrogen-containing solvent, a compound containing at least one nitrogen atom in the molecule and exhibiting the above-mentioned water solubility can be suitably used. Examples of such nitrogen-containing solvents include N-methylpyrrolidone, ε-caprolactam, 2-pyrrolidone, N-N-dimethylacetamide, N-N-diethylformamide, N-methylformamide, N-methylacetamide, acetamide, acetonitrile, methylamine, dimethylamine, trimethylamine, ethylenediamine, and hydrazine. In addition, even if a solvent has a nitrogen atom, the solvents that fall under the above-mentioned ether solvents, alcohol solvents, ketone solvents, or ester solvents are not included in the nitrogen-containing solvents of the present invention.
[0036] As the organic solvent that can be used in the present invention, an organic solvent consisting of a compound having a plurality of functional groups (for example, an organic solvent consisting of a compound having two or more of the functional groups exemplified above) can also be suitably used. Examples of such organic solvents include 2-methoxyethanol, 2-ethoxyethanol, 2-(methoxy)ethanol, 2-isopropoxyethanol, 2-butoxyethanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monoethyl ether, polyethylene glycol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, polypropylene glycol, dipropylene glycol, dipropylene glycol monomethyl ether, and diacetone alcohol. These organic solvents are categorized into the respective organic solvent types according to the above explanation.
[0037] <Water> The polar medium constituting the slurry of the present invention contains water. When ammonia water is used as the ammonia source, the water in the ammonia water constitutes the water in the slurry. The water in the slurry may contain water other than ammonia water that is mixed separately. Although there is no particular limitation on the water used, it is preferable to use water from which ionic components have been removed, such as distilled water, ion-exchanged water, etc. The degree of ion removal is preferably such that the ionic conductivity of the water is 10 μS / m or less, more preferably 5 μS / m or less, and even more preferably 2 μS / m or less.
[0038] The proportion of water (content: mass%) in the polar medium constituting the slurry of the present invention is preferably 90 mass% or less, more preferably 80 mass% or less, also preferably 75 mass% or less, and may be 70 mass% or less, from the viewpoint of improving the dispersibility of the polyvalent metal-fixed smectite. From the same viewpoint, the proportion of water in the polar medium constituting the slurry of the present invention is preferably 4 mass% or more, more preferably 7 mass% or more, even more preferably 10 mass% or more, and even more preferably 15 mass% or more.
[0039] The total content of water and organic solvent in the polar medium constituting the slurry of the present invention is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, still more preferably 90% by mass or more, and also preferably 95% by mass or more. It is also preferable that the remainder of the polar medium, excluding ammonia, is entirely composed of water and organic solvent.
[0040] A polar medium containing ammonia, water, and an organic solvent is used, and the polyvalent metal-fixed smectite is mixed therewith. As described below, this is subjected to a heat treatment at 35 to 100°C to cause the polar medium to act on the polyvalent metal-fixed smectite, whereby the organic solvent acts in a chain reaction with the ammonia in the presence of water on the polyvalent metal-fixed smectite, thereby sufficiently finely refining the polyvalent metal-fixed smectite in the slurry.
[0041] <Other ingredients> The polar medium constituting the slurry of the present invention can contain various components in addition to ammonia, organic solvent, and water, as long as the effects of the present invention are not impaired. In consideration of improving the dispersibility of the polyvalent metal-fixed smectite, for example, the polar organic solvent having a formamide group described in JP 2015-147300 A, or acetonitrile or methyl ethyl ketone described in JP 2018-83728 A can be contained. Although it depends on the use of the slurry of the present invention, from the viewpoint of biological safety, for example, it is preferable that the polar medium constituting the slurry of the present invention does not contain any of a polar organic solvent having a formamide group, acetonitrile, and methyl ethyl ketone.
[0042] In addition, the slurry of the present invention may further contain a silane coupling agent, a crosslinking agent, an organic polymer, a non-swelling silicate compound, silica, a surfactant, inorganic nanoparticles, etc., within a range that does not substantially impair the effects of the present invention.
[0043] If the slurry of the present invention has a high clay concentration, it can be diluted to a desired concentration before use.
[0044] [Method for producing smectite slurry] Next, a method for producing the slurry of the present invention will be described. The slurry of the present invention can be obtained by mixing the components (raw materials) constituting the slurry and subjecting them to a heat treatment at 35 to 100° C. That is, through the above heat treatment, the organic solvent and ammonia in the polar medium act on the polyvalent metal-fixed smectite in the presence of water and penetrate between the layers with high efficiency, thereby obtaining a slurry in which the polyvalent metal-fixed smectite is stably dispersed in a finer particle state. That is, in order to obtain the slurry of the present invention, this heat treatment is currently an essential step.
[0045] The method of mixing the raw materials (the method of mixing before the heat treatment) is not particularly limited, and the raw materials can be mixed simultaneously or in any order. In addition, when mixing, a general bladed agitator, homomixer, universal mixer, planetary mixer, Eirich mixer, etc. can be used. Among them, a universal mixer and a planetary mixer that can mix efficiently even when the smectite concentration exceeds 20 mass% can be preferably used. The temperature at which the raw materials are mixed is preferably less than 40°C, and more preferably less than 30°C.
[0046] The heat treatment at 35 to 100° C. after mixing the above-mentioned raw materials is not particularly limited as long as it is a treatment in which heating is performed at a temperature of 35 to 100° C. From the viewpoints of both dispersibility and handleability of the polyvalent metal-fixed smectite, the heat treatment temperature is more preferably 40 to 90° C., more preferably 50 to 90° C., even more preferably 55 to 85° C., and still more preferably 60 to 85° C. The time of the heat treatment at 35 to 100 ° C. is not particularly limited as long as the polyvalent metal-fixed smectite can be finely divided to a desired particle size, and is appropriately set according to the heating temperature and the like. The heat treatment time is usually 2 hours or more, more preferably 4 hours or more, and even more preferably 6 hours or more. The longer the heat treatment time, the more likely it is that the polyvalent metal-fixed smectite can be finely divided. For example, even if the heat treatment temperature is a relatively low temperature of 35 to 50 ° C., the heat treatment time can be set to 10 hours or more, preferably 15 hours or more, more preferably 20 hours or more, and even more preferably 24 hours or more, so that the desired fine particle size of the polyvalent metal-fixed smectite can be more reliably achieved. There is no particular limit to the upper limit of the heat treatment time, which is usually 50 hours or less, and sufficient dispersibility can be achieved even if it is 30 hours or less. In addition, the heat treatment time tends to be shortened by performing high-temperature high-pressure treatment using an autoclave or the like. In addition, when a high-temperature, high-pressure vessel such as an autoclave is not used, the heating temperature may be set to a temperature equal to or lower than the boiling point of the organic solvent and water contained in the slurry. The heat treatment time at 35 to 100° C. is usually 2 to 50 hours, preferably 4 to 40 hours, more preferably 6 to 30 hours, and even more preferably 10 to 30 hours. This heat treatment may be carried out either statically or with stirring.
[0047] By the above heat treatment, the polyvalent metal-fixed smectite can be stably dispersed in the dispersion medium as fine particles (dispersoid) having a particle size of 20 μm or less in the slurry of the present invention obtained. The preferred particle size of the polyvalent metal-fixed smectite in the slurry is as described above.
[0048] The slurry of the present invention can form a clay film with excellent water resistance simply by forming the slurry on a substrate and drying it to a desired level. In other words, the slurry of the present invention is unlikely to absorb water even when it comes into contact with moisture, and can be suitably used for forming a clay film with high durability. The clay film prepared using the slurry of the present invention can be used, for example, as a packaging film, an electronic substrate, a flame retardant film, a water vapor barrier film, an insulating film, a coated film, and the like. EXAMPLES
[0049] The present invention will be described in more detail below based on examples, but the present invention is not limited to these.
[0050] <Preparation of polyvalent metal smectite> The raw material polyvalent metal smectite was obtained by ion exchange treatment of natural Na-montmorillonite (product name: Kunipia F, manufactured by Kunimine Kogyo Co., Ltd.). The obtained polyvalent metal smectite having each cation was subjected to leaching cation analysis to examine the exchangeable cation composition. More specifically, leaching of the cations present between the layers was carried out using 1M ammonium acetate or 1M sulfuric acid (only Al-montmorillonite) for 4 hours, and the leaching solution was analyzed by a 4100MP-AES spectrometer (manufactured by Agilent Technologies Co., Ltd.) to examine the exchangeable cation composition. Similarly, the polyvalent metal smectite obtained was subjected to a cation exchange capacity measurement test to measure the CEC. The measurement was performed according to the method described in the Japan Bentonite Industry Association's standard test method JBAS-106-77. More specifically, the cations present between the layers were completely exchanged for ammonium ions using 1M ammonium acetate, and then the ammonium ions were expelled again using potassium ions derived from a KCl (potassium chloride) solution, and the amount of potassium ions was measured using an ammonium electrode to quantify the CEC. The results are shown in Table 1 below.
[0051] [Table 1]
[0052] <Preparation of polyvalent metal-fixed smectite> 100 g of each of the polyvalent metal-type smectites obtained by the above methods was placed in an electric furnace (muffle furnace, FO410, manufactured by Yamato Scientific Co., Ltd.) and heated at a rate of 10°C / min until the firing temperatures shown in Table 2 were reached, and then the same temperatures were maintained for 24 hours for heat treatment. Thereafter, the samples were allowed to cool and the fired samples were collected at 50°C or less to obtain polyvalent metal-fixed smectites. The CEC of the obtained polyvalent metal-fixed smectite was quantified according to the above-mentioned CEC measurement method, and the results are shown in Table 2 below.
[0053] [Preparation of slurry] <Example 1> 38.0 g of distilled water, 2.0 g of 28% ammonia water (Kanto Chemical Co., Ltd.), 20 g of Mg-fixed montmorillonite (CEC: 35 meq / 100 g), and 40.0 g of acetone (Kanto Chemical Co., Ltd.) were placed in a beaker and stirred at 25° C. for 1 hour at a rotation speed of 700 rpm using a stirrer (product name: TORNAD PM-201, AS ONE Co., Ltd.). The resulting mixture was placed in a glass container (KIMAX (registered trademark) heat-resistant wide-mouth bottle 100 ml, KIMBLE Co., Ltd.) and subjected to heat treatment at 50° C. for 24 hours in a constant temperature and sound oscillating machine (product name: DKM400, Yamato Scientific Co., Ltd.). Thus, the polyvalent metal-fixed smectite slurry of Example 1 was obtained. In the smectite slurry of Example 1, the amount of ammonia blended per 1 g of Mg-fixed montmorillonite was 1.65 mmol (the same applies to each of the Examples and Comparative Examples described later except for those in which ammonia was not added).
[0054] The smectite slurries of Examples 2 to 9 and Comparative Examples 1 to 9 were obtained by the following methods. The organic solvents used were all reagents manufactured by Kanto Chemical Co., Ltd. <Examples 2 to 9> Various polyvalent metal-fixed smectite slurries were obtained in the same manner as in Example 1, except that the types of polyvalent metal-fixed smectite and organic solvent, the amounts of each main component, and the heating temperature were changed to the conditions shown in Table 2 below.
[0055] <Comparative Examples 1 and 8> Polyvalent metal-fixed smectite was obtained in the same manner as in Examples 1 and 8, except that no organic solvent was used when preparing the polyvalent metal-fixed smectite slurry, and the same amount of distilled water as the organic solvent used in Examples 1 and 8 was further added to make the smectite content in the slurry the same.
[0056] <Comparative Examples 2, 5, and 7> Polyvalent metal-fixed smectite was obtained in the same manner as in Examples 2, 5, and 7, except that distilled water was not used when preparing the polyvalent metal-fixed smectite slurry, and the same amount of organic solvent as the distilled water used in Examples 2, 5, and 7 was further added to make the smectite content in the slurry the same.
[0057] <Comparative Examples 3 and 9> A polyvalent metal-fixed smectite was obtained in the same manner as in Examples 3 and 9, except that the polyvalent metal-fixed smectite slurry was prepared without heating and was left at room temperature of 25° C. for 24 hours before evaluation.
[0058] <Comparative Examples 4 and 6> Polyvalent metal-fixed smectite was obtained in the same manner as in Examples 4 and 6, except that ammonia water was not used when preparing the polyvalent metal-fixed smectite slurry, and the same amount of water as the ammonia water used in Examples 4 and 6 was further added to make the smectite content in the slurry the same.
[0059] [Test Example 1] Particle size of polyvalent metal-fixed smectite (dispersoid) The slurries of Examples 1 to 9 and Comparative Examples 1 to 9 were diluted with water to a solid content of 2% by mass, and the median diameter of the polyvalent metal-fixed smectite was measured by wet particle size measurement. This median diameter is based on volume. A laser diffraction / scattering type particle size distribution measuring device (LA-950V2, manufactured by HORIBA) was used to measure the median diameter. The results are shown in Table 2 below.
[0060] [Test Example 2] Dispersion stability The obtained slurries of Examples 1 to 9 and Comparative Examples 1 to 9 were placed in glass containers and allowed to stand for 24 hours at 25° C. After standing for 24 hours, the dispersion state of the polyvalent metal-immobilized smectite was visually observed, and the dispersion stability was evaluated according to the following evaluation criteria. The results are shown in Table 2 below. - Evaluation criteria for dispersion stability - ◯: No layer separation occurred and the dispersion was stable. ×: Layer separation occurred and precipitation was observed.
[0061] [Table 2]
[0062] As shown in Table 2 above, when the polar medium does not contain an organic solvent, the particle size of the polyvalent metal-fixed smectite, which is the dispersoid, cannot be made to the desired small particle size (20 μm or less) even if the slurry is heated, and the dispersion stability is also poor (Comparative Examples 1 and 8). Even when the polar medium contains an organic solvent, when water is not blended, the particle size cannot be made to the desired small particle size as in Comparative Examples 1 and 8, and the dispersion stability is also poor (Comparative Examples 2, 5, and 7). Even when the polar medium contains water and an organic solvent, when it does not contain ammonia, the particle size cannot be made to the desired small particle size as in the above comparative examples, and the dispersion stability is also poor (Comparative Examples 4 and 6). Furthermore, even when the polar medium contains water, an organic solvent, and ammonia, when the heating treatment is not performed, the particle size is large and the dispersion stability is poor (Comparative Examples 3 and 9). In contrast, by mixing a polar medium with a combination of water, an organic solvent, and aqueous ammonia, and then subjecting the slurry to a heat treatment, the particle size of the polyvalent metal-fixed smectite, which is the dispersoid, can be made to a desired small particle size, and a slurry with excellent dispersion stability can be obtained (Examples 1 to 9).
Claims
1. A smectite slurry comprising a polyvalent metal-fixed smectite having a cation exchange capacity of 50 meq / 100 g or less dispersed in a polar medium containing ammonia, water, and a polar organic solvent, the polyvalent metal-fixed smectite in the dispersed state having a particle size of 20 μm or less, and the smectite being montmorillonite.
2. 2. The smectite slurry according to claim 1, wherein the polyvalent metal-fixed smectite is a divalent metal-fixed smectite and / or a trivalent metal-fixed smectite.
3. 3. The smectite slurry according to claim 2, wherein the divalent metal-fixed smectite is one or more of Ca-fixed smectite, Mg-fixed smectite, Fe-fixed smectite, Zn-fixed smectite and Cu-fixed smectite.
4. The smectite slurry according to claim 2 or 3, wherein the trivalent metal-fixed smectite is Al-fixed smectite and / or Fe-fixed smectite.
5. The smectite slurry according to any one of claims 1 to 4, wherein the polar organic solvent is one or more of an ether solvent, an alcohol solvent, a ketone solvent, an ester solvent, and a nitrogen-containing solvent.
6. The smectite slurry according to any one of claims 1 to 5, wherein the content of the water in the polar medium is 4 to 90 mass%.
7. 7. The smectite slurry according to claim 1, wherein the content of the ammonia in the smectite slurry is 0.1 mmol or more per 1 g of the polyvalent metal-fixed smectite.
8. A clay film using the smectite slurry according to any one of claims 1 to 7.
9. A method for producing a smectite slurry includes mixing a polyvalent metal-fixed smectite having a cation exchange capacity of 50 meq / 100 g or less, ammonia, water, and a polar organic solvent, and subjecting the mixture to a heat treatment at 35 to 100° C. to obtain a slurry in which the polyvalent metal-fixed smectite is dispersed in the polar medium, wherein the proportion of water in the polar medium is 4 mass % or more, the particle size of the polyvalent metal-fixed smectite dispersed in the polar medium is 20 μm or less, and the smectite is montmorillonite.
10. 10. The method for producing a smectite slurry according to claim 9, wherein the polyvalent metal-fixed smectite is a divalent metal-fixed smectite and / or a trivalent metal-fixed smectite.
11. The method for producing a smectite slurry according to claim 10, wherein the divalent metal-fixed smectite is one or more of Ca-fixed smectite, Mg-fixed smectite, Fe-fixed smectite, Zn-fixed smectite and Cu-fixed smectite.
12. The method for producing a smectite slurry according to claim 10 or 11, wherein the trivalent metal-fixed smectite is Al-fixed smectite and / or Fe-fixed smectite.
13. The method for producing a smectite slurry according to any one of claims 9 to 12, wherein the polar organic solvent is one or more of an alcohol solvent, a ketone solvent, an ether solvent, an ester solvent, and a nitrogen-containing solvent.
14. The method for producing a smectite slurry according to any one of claims 9 to 13, wherein the content of the water in the polar medium is 4 to 90 mass%.
15. The method for producing a smectite slurry according to any one of claims 9 to 14, wherein the amount of the ammonia mixed is 0.1 mmol or more per 1 g of the polyvalent metal-fixed smectite.
Citation Information
Patent Citations
Method for preparing smectite inorganic gel by mechanochemical modification
CN104760969A
Preparation method of magnetic bentonite
CN104891513A
Clay film and its manufacturing method
JP2008247719A
Synthetic smectite and dispersion liquid containing this, clay film, waterproof film, and method of producing synthetic smectite and waterproof film
JP2009107907A
Montmorillonite slurry, clay film, and method for production of montmorillonite slurry
JP2015147300A